Truth‐Grounding and Transitivity. (2nd January 2014) - Tahko, Tuomas E.
Abstract It is argued that if we take grounding to be univocal, then there is a serious tension between truth‐grounding and one commonly assumed structural principle for grounding, namely transitivity. The primary claim of the article is that truth‐grounding cannot be transitive. Accordingly, it is either the case that grounding is not transitive or that truth‐grounding is not grounding, or both.